Pemanfaatan Media Sosial Instagram Dalam Meningkatkan Kreativitas Siswa Pada Mata Pelajaran PAI - Maria, Anly; Yudita, Rosa (STAI Al-Musaddadiyah Garut, 2023)
Student creativity is a skill that students have to create or produce something new. Creativity can also be defined as a person's ability to see various possible solutions to problems by creating something new, both in the form of ideas and in the form of real works, both new works and combinations of existing things. However, in fact the learning creativity of students at SMA Plus Al-Qomariyah Garut shows that it is still low, this is evidenced by the findings of researchers when learning takes place. Students who have shown creativity are only about 25% and 75% of students still have not shown creativity. Social media Instagram is one of the developments in social media which is one of the trending choices and is widely used by students every day. Thus the researcher will try to use product evaluation by assigning students to create da'wah content by posting da'wah videos on the Instagram social media platform. The purpose of this study was to find out the use of Instagram social media in increasing student creativity in PAI subjects, Dakwah material K.D 1.1 in Class X IPS 1 SMA Plus Al-Qomariyah Sukaresmi Garut. The method used is Classroom Action Research (CAR), which is a form of reflective and collective research conducted by researchers in social situations to improve their social practice reasoning. The data sources used in this study are primary sources and secondary sources. Data collection techniques in this study were observation and documentation. The data analysis techniques in this study are planning, action, observation, and reflection. Utami Munandar argues that creativity is the result of interactions between individuals and their environment. The results of this study indicate that the use of Instagram social media can increase student creativity by fulfilling 5 indicators of student creativity including; broad and deep curiosity, often asks good questions, gives many ideas or suggestions for a problem, is able to see a problem from various perspectives/points of view, and has imagination. Keywords: Islamic Education: Student creativity: Social media Instagram: dakwah